2005
DOI: 10.1002/zaac.200500100
|View full text |Cite
|
Sign up to set email alerts
|

The Cadmium Oxide Route to Alkali Metal Oxometallates with Uncommon Structural Features

Abstract: The aim of this research report is to give an introduction to a specific solid state reaction applied in the field of alkali metal rich transition metal compounds. The approach is an explorative investigation of the oxidation of transition metals with CdO in the presence of alkali metal oxides and / or compounds with complex anions such as Na2SO4. Thereby, a range of unusual compounds have been obtained and structurally characterized. In particular, low valences and uncommon coordination numbers (C.N.) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The chemicals were commercial grade and used as received: sodium oxide (Alfa Aesar, Na 2 O 86–88 %), CdO (Alfa Aesar, 99.998 %), iron powder (Alfa Aesar, 99 %) NaOH (EMD) and Ag (Oegussa). Red crystals of Na 5 [FeO 3 ][OH] were prepared by the reaction of Na 2 O (341 mg), iron powder (140 mg), CdO (320 mg), and NaOH (100 mg) as starting materials in a 2.2:1:1:1 molar ratio as previously described via the CdO route13 in sealed Ag containers encapsulated in silica glass ampoules under an inert gas atmosphere (Ar). The reaction was kept at 450 °C for 5 days, and then cooled to 200 °C with a rate of 40 K · d –1 .…”
Section: Methodsmentioning
confidence: 99%
“…The chemicals were commercial grade and used as received: sodium oxide (Alfa Aesar, Na 2 O 86–88 %), CdO (Alfa Aesar, 99.998 %), iron powder (Alfa Aesar, 99 %) NaOH (EMD) and Ag (Oegussa). Red crystals of Na 5 [FeO 3 ][OH] were prepared by the reaction of Na 2 O (341 mg), iron powder (140 mg), CdO (320 mg), and NaOH (100 mg) as starting materials in a 2.2:1:1:1 molar ratio as previously described via the CdO route13 in sealed Ag containers encapsulated in silica glass ampoules under an inert gas atmosphere (Ar). The reaction was kept at 450 °C for 5 days, and then cooled to 200 °C with a rate of 40 K · d –1 .…”
Section: Methodsmentioning
confidence: 99%
“…It was found that large excess of Na 2 O and Na 2 CO 3 provided good quality single crystals of suitable size (e.g., ≈ 0.12 × 0.12 × 0.1 mm) for spectroscopic characterization. The synthetic approaches involved the use of binary compounds, Cu 2 O for all cuprates as starting materials whereas for M = Co, Ni the CdO route was applied. All reactions were carried out under an inert gas atmosphere (Ar) in sealed Ag containers which were encapsulated in silica glass ampules.…”
Section: Methodsmentioning
confidence: 99%
“…Rb 6 CdO 4 , Rb 2 CdO 2 or Rb 2 Cd 2 O 3 (Baier et al 1987). These intermediate products react with the vanadium metal in a redox reaction (Mo ¨ller, 2005), yielding oxovanadate(s) and cadmium metal. Here, this process was not complete and we obtained Rb[NaCd 3 O 4 ], a rather alkali metal-poor compound.…”
Section: Methodsmentioning
confidence: 99%